Issue Information TOC. Issue 1 (19th June 2019) - Unknown
Abstract : Cover : In Stansfield et al. (https://doi.org/10.1002/cpbi.76 ) image shows composite MD plot with significant differentially interacting regions highlighted. Highlighted points display where the differential interactions are occurring in relation to unit genomic distance on the x axis and log2 fold change on the y axis. Points highlighted in yellow are moderately significant, while points highlighted in red are highly significant.